Herpes Zoster Following Covaxin Receipt - Muhie OA (Dove Medical Press, 2021)
Oumer Abdu Muhie,1 Haylemariam Adera,1 Eyob Tsige,1 Aschalew Afework2 1Department of Internal Medicine, GAMBY Teaching General Hospital, Bahir Dar, Ethiopia; 2Department of Public Health, GAMBY Teaching General Hospital, Bahir Dar, EthiopiaCorrespondence: Oumer Abdu Muhie Tel +251 921638680Email umerabdu88@gmail.comBackground: Herpes zoster is a reactivation of varicella zoster virus infection. We presented this case since it occurred after the receipt of Covaxin vaccine. There are few case reports of herpes zoster after the receipt of COVID-19 vaccine in the literature.Case Presentation: We presented a case of herpes zoster in a 72-year-old lady after she received the first dose of the vaccine for COVID-19. She had post-herpetic neuralgia.Conclusion: It is evident that VZV reactivation is one of the untoward events of the COVID-19 vaccine. However, it is wise to do large epidemiologic studies to check how common herpes zoster is after the receipt of COVID-19 vaccine.Keywords: herpes zoster, vaccine, COVID-19, Ethiopia